2004
DOI: 10.1038/sj.onc.1208032
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation of genes that regulate cytokine signaling in lymphoid and hematopoietic tumors

Abstract: The perturbations of the cytokine signaling pathway play an important role in lymphoid/hematopoietic tumors. Aberrant promoter methylation is the major mechanism of gene silencing in tumors. We examined 150 lymphoid/ hematopoietic tumors or potential premalignant specimens, 55 control specimens and 12 EBV-transformed B lymphoblastoid cultures and 10 lymphoma/leukemia (L/L) or multiple myeloma (MM) cell lines for the methylation (and, in cell lines, of the expression status) of three genes involved in the cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 25 publications
3
25
1
Order By: Relevance
“…We failed to detect decreased expression of these phosphatases between TgSTAT5A* leukemic cells and normal lymphoid cells, indicating that loss of expression of these phosphatases is not responsible for enhanced STAT5 tyrosine phosphorylation in TgSTA-T5A* leukemia. The genes encoding SHPTP1 and SOCS1, two negative regulators of the JAK/STAT pathway, are frequently methylated in human B-cell leukemia/lymphoma (Reddy et al, 2005). However, we failed to detect any defect in SHPTP1 and SOCS1 expression in TgSTAT5A* leukemic cells, indicating that inactivation of these genes is unlikely to be instrumental in STAT5 hyperactivation in STAT5A* (Fleming et al, 2004).…”
Section: Discussioncontrasting
confidence: 61%
“…We failed to detect decreased expression of these phosphatases between TgSTAT5A* leukemic cells and normal lymphoid cells, indicating that loss of expression of these phosphatases is not responsible for enhanced STAT5 tyrosine phosphorylation in TgSTA-T5A* leukemia. The genes encoding SHPTP1 and SOCS1, two negative regulators of the JAK/STAT pathway, are frequently methylated in human B-cell leukemia/lymphoma (Reddy et al, 2005). However, we failed to detect any defect in SHPTP1 and SOCS1 expression in TgSTAT5A* leukemic cells, indicating that inactivation of these genes is unlikely to be instrumental in STAT5 hyperactivation in STAT5A* (Fleming et al, 2004).…”
Section: Discussioncontrasting
confidence: 61%
“…Here, we observed that dormant tumor cells progressively methylate the SOCS1 gene, ultimately silencing expression. Methylation of the SOCS1 gene has been reported in several human tumors, including lymphoid and myeloid hematologic malignancies (33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Our findings suggest a possible role in tumor dormancy.…”
Section: Discussionsupporting
confidence: 60%
“…A large number of studies have been focused on the role of SHP-1 in hematopoietic cells, 13,[34][35][36][37] whereas the role of SHP-1 in epithelial cells and epithelium-derived carcinomas is less well characterized. In hematopoietic cells, SHP-1 has been suggested to contribute to the termination of mitogenic signals of growth factors by dephosphorylating critical phosphorylated molecules.…”
Section: Discussionmentioning
confidence: 99%